Formation of wide negative streamers in air and helium: the role of fast electrons. (29th December 2022) - Babaeva, N Yu; Naidis, G V; Tereshonok, D V; Tarasenko, V F; Beloplotov, D V; Sorokin, D A
Abstract: Available experimental data show that the use of voltage pulses with subnanosecond rise times and amplitudes that essentially exceed the breakdown voltage leads to the formation of wide spherical or conical streamers. In this paper, the structure and dynamics of atmospheric pressure wide negative streamers in air and helium by applying high overvoltages with a short rise time to a sharp needle electrode are investigated experimentally and computationally. In the simulations, the two-dimensional fluid and kinetic electron Monte Carlo simulation models are used. All the streamers were simulated with the conventional photoionization term S ph that was never turned off. By including an additional source S MC, responsible for the generation of fast electrons, wide and diffuse streamers are obtained. We compare the shapes, width and velocities of conventional streamers in air and helium with those for streamers driven by fast electrons. We show that a conventional streamer in air has a cylindrical form. The conventional streamer in helium is wider than that in air and has a shape of an expanding cone. While accounting for fast electrons, different streamer shapes were obtained. In air, the gap was closed by a spherical streamer. In helium, the shape of a streamer resembles that of a pumpkin. We also demonstrate that near the flat anode, velocities of conventional streamers in air and helium were as high as 5 × 10 9 cm s −1 and reached values greater than 10 10 cm s −1 when fast electrons were taken into account. By the application of high (by a factor of four or greater) overvoltages to a sharp needle electrode, the formation of a discharge with several parallel streamers was observed. In this regime, the trajectories of fast electrons originated not only from the cathode, but also from the region of a streamer front where the electric field is high. As a result, the so-called diffuse discharge was formed with high intensity plasma channels surrounded by an aureole of smaller electron density.